Faktor Sosio-Ekonomi yang Mempengaruhi Kualitas Tidur Pada Individu Cerai Mati di Indonesia - Salim, Prasetya Rahman; Avia, Zahra; Sihaloho, Estro Dariatno (Universitas Negeri Padang, 2023)
Losing a spouse is one of the most stressful events in a person's life. Meanwhile, stress is one of the triggers for health problems. Using IFLS 2014 as data and logistic regression as a method, we found that depressive symptoms, smoking habits, education level, and living in urban areas have a positive correlation with the probability of widows having poor sleep quality. This can increase the probability of having diabetes and cardiovascular diseases that can lead to death. The support of the closest family is expected to help the widow have better sleep quality.